Race for your life, Charlie Brown [videorecording (Blu-Ray)] - Schulz, Charles M. (Charles Monroe), 1922-2000 (Paramount Home Entertainment, 2021)
Charlie Brown, Lucy, Snoopy and the rest of the 'Peanuts' gang get into a wild adventure on a raft at summer camp, learning courage, leadership, and teamwork along the way.